Studi Komparatif: Urgensi Reformulasi Sanksi Pidana Deepfake Dalam Kuhp Dan UU ITE - Ramadan, Muhammad Ijzlal; Wahyudi, Endik (Fakultas Hukum Dehasen, 2025)
This research examines the urgency of reformulating criminal sanctions for digital crimes involving deepfake technology within the framework of Indonesian law, particularly the Law on Electronic Information and Transactions (UU ITE) and the Indonesian Penal Code (KUHP). The primary focus is to analyze the current legal framework in Indonesia and compare it with regulations in South Korea and the United States. This study employs a normative juridical method with a statutory, conceptual, and comparative approach. The findings reveal that Indonesia does not yet have specific provisions regulating deepfake, whereas several countries have enacted more adaptive legal instruments. Therefore, comprehensive legal reform is necessary to anticipate the negative impacts of artificial intelligence technologies on privacy rights, democratic integrity, and public order.